Long-term management of contaminated sites - Leschine, Thomas M. (Amsterdam ; London : Elsevier JAI, 2007)
Even today, many people think of 'social problems' as involving poor and powerless individuals in society. "Research in Social Problems and Public Policy" seeks to improve the balance by adding a focus on important and powerful institutions. Such organizations often play key roles in managing, and mismanaging, the ways in which some of today's most important social problems are handled by the public policy system. The series presents papers that discuss policy sciences, public policy analysis and public management. This volume addresses operations and design issues for government organizations.
Introduction: long--term management of contaminated sites / Thomas M. Leschine -- Public participation in long--term management. The Hanford openness workshops: fostering open and transparent long--term decision making at the Department of Energy / Christina H. Drew ... [et al.] -- Competing perspectives on a process for making remediation and stewardship decisions at the Rocky Flats environmental technology site / Seth Tuler and Thomas Webler -- Long--term management in practice: lessons from the sites. Long--term stewardship for the Hanford nuclear site / Max S. Power -- CERCLA remedy selection lessons: the Shattuck site / Elizabeth K. Hocking -- Scientific and technical perspectives on long--term management. A sustainable environmental protection system for the management of residual contaminants / Kevin M. Kostelnik ... [et al.] -- Ecological considerations for evaluating current risk and designing long--term stewardship on Department of Energy lands / Joanna Burger ... [et al.] -- The lessons of history. Living in a nuclear landscape: rehabilitation and resettlement of proving grounds in Australia and islands of the western Pacific / Anne Ballou ... [et al.] -- The challenges ahead. Vulnerabilities and uncertainties in long--term stewardship / Curtis Travis -- A 19--year perspective on long--term care issues / Denise Bierley -- Long--term stewardship and risk management: analytic and policy challenges / Eugene A. Rosa.
Includes bibliographical references.
Description based on print version record.
Keywords: Hazardous waste sites -- Management; Hazardous waste site remediation -- Management; Waste management; Pollution & threats to the environment; Technology & Engineering -- Environmental -- Waste Management